Mind-muscle-environment interactions: psychophysiological determinants of optimal pacing in Olympic winter endurance sports - Edholm, P.; Bouten, L. J. L.; Holmberg, H.-C.; Losnegard, T.; Hettinga, F. J. (Scandinavian Journal of Medicine & Science in Sports, 2026)
Pacing is a critical determinant of performance in Olympic endurance winter sports such as cross-country skiing, biathlon, and speed skating. Although the physiological ("engine") and psychological ("operator") determinants of pacing have frequently been examined in isolation, growing evidence highlights the need for an integrated psychophysiological perspective. This structured narrative review first outlines the defining characteristics of Olympic winter sports and, within this context, synthesizes current knowledge on the psychophysiological mechanisms governing pacing to inform optimal preparation strategies. We describe how the physiological engine, encompassing energy systems, fatigue, and afferent feedback, and the psychological operator, involving self-regulation, expectations, and cognitive-affective processes, interact to shape pacing behavior. Moreover, the distinctive demands of winter endurance events necessitate consideration of environmental factors such as head-to-head racing formats, variable weather conditions, and undulating terrain. The affordance competition hypothesis is proposed as a unifying framework for understanding pacing as a continuous decision-making process driven by dynamic mind-muscle-environment interactions. Finally, practical recommendations for athletes and coaches preparing for the Milano-Cortina 2026 Winter Olympic Games are presented, advocating a phased training approach that integrates physiological and psychological development within ecologically valid environments. Future research should prioritize real-world competition settings, neurocognitive mechanisms, and underrepresented populations, including women and para-athletes. We conclude that Olympic success in modern endurance winter sports depends on mastering an integrated psychophysiological control system, where performance is determined by both physical capacity and its effective regulation under varying environmental conditions.